The Role of Point-of-care Glucose Monitoring Devices in Initiating Treatment for Neonatal Hypoglycaemia: A Cross-sectional Study - Amina Shamsudeen; Roseline K Madathil; Kunjumol P Mathew; Krishna K Diwakar (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: Detection and prompt management of hypoglycaemia among at-risk and symptomatic neonates is crucial to prevent neurodevelopmental morbidity. Laboratory-based Formal Random Blood Sugar (FRBS) is the gold standard for estimating Blood Glucose (BG) levels. Point-of-care Glucose Monitoring Devices (POCGMD)/glucometers that provide immediate results are used as surrogates. Glucometers provide widely variable and overestimated values of BG. Therefore, when using glucometers, a higher cut-off value for glucose may have to be considered as the operational threshold for hypoglycaemia. Aim: To evaluate the adequacy of POCGMD for detecting the threshold levels for treating neonatal hypoglycaemia by assessing the agreement with FRBS values. Materials and Methods: This cross-sectional study was conducted in the Neonatal Intensive Care Unit (NICU), Malankara Orthodox Syrian Church Medical College, Kerala, India, from July 2022 to October 2022. A total of 258 infants at risk for and with hypoglycaemia were selected through convenience sampling. BG was estimated simultaneously in the laboratory and with a POCGMD. Three different types of POCGMDs were consecutively used in the unit during the study period. FRBS and POCGMD values were evaluated using Spearman's rank correlation coefficient. The agreement between the gold standard FRBS and POCGMD values was ascertained through Bland-Altman plots. Receiver Operating Characteristic (ROC) curves identified the higher cut-off levels for each of the brands of POCGMDs at which intervention for hypoglycaemia should be initiated. Results: The present study showed a strong positive correlation between the standard laboratory FRBS and POCGMD measurements. However, there was no agreement between FRBS and POCGMD values according to Bland-Altman graphs. The mean bias values for BG were higher for glucometers. The ROC curves identified 62 mg/dL for Accu-Check, 59 mg/dL for Contour, and 53 mg/dL for AccuSure as the optimum cut-off corresponding to the operational threshold of FRBS of 45 mg/dL. Conclusion: Glucometers overestimate BG values and miss the biochemical thresholds for treating neonatal hypoglycaemia. When POCGMDs are used, a higher cut-off value may have to be considered as the operational threshold for initiating treatment for hypoglycaemia.